STRATEGI KOMUNIKASI PESAN KREATIF RECIPROCITY PRINCIPLE DALAM PROMOSI PRODUK DI MEDIA SOSIAL TIKTOK - Reni Mustikasari; Ani Yuningsih; Udung Noor Rosyad (Interaksi: Jurnal Ilmu Komunikasi, 2023)
TikTok is one of the most widely used social media in Indonesia, especially the younger generation. This media is used as a place to channel the creativity of its users. Recently, TikTok has also been used for business activities, one of which is promotion. The subjects in this study are businesses that are managed by individuals using digital media as a means of promoting their products. The promotion carried out by Bouquet by Namalia is a creative communication strategy through the use of the principle of reciprocity, in which creativity and reciprocity are used as the basis for creating promotional content. The purpose of this study is to describe how the process of managing reciprocal creative communication strategies carried out by Bouquet by Namalia as an individual business is managed through the use of digital media to develop its business. This study uses qualitative methods with data collection techniques including in-depth interviews, literature study and observation. The result of this research is the creation of a creative communication strategy management process model with the principle of reciprocity in promotion on TikTok social media.